2013
DOI: 10.4132/koreanjpathol.2013.47.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability Status in Gastric Cancer: A Reappraisal of Its Clinical Significance and Relationship with Mucin Phenotypes

Abstract: BackgroundGastric cancers with microsatellite instabilities (MSI) have been reported to be associated with favorable prognosis. However, the significance of the effect of MSI on the clinicopathological features, as well as its association with mucin phenotype, remains unclear.MethodsMSI status was assessed in 414 cases of gastric cancer using polymerase chain reaction analysis of five microsatellite loci, as recommended by National Cancer Institution criteria. The expression of mucins (MUC5AC, MUC6, MUC2, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
70
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 24 publications
17
70
1
4
Order By: Relevance
“…Recent studies have demonstrated the predictive value of immunohistochemistry which includes analysing four proteins (MLH1, MSH2, MSH6 and PMS2) which is virtually equivalent to MSI testing (Fig. 2) [11,35,36]. Microsatellite analysis and immunohistochemical staining are in agreement in more than 90% of GCs [37].…”
Section: Microsatellite Instability In Gastric Cancermentioning
confidence: 70%
See 4 more Smart Citations
“…Recent studies have demonstrated the predictive value of immunohistochemistry which includes analysing four proteins (MLH1, MSH2, MSH6 and PMS2) which is virtually equivalent to MSI testing (Fig. 2) [11,35,36]. Microsatellite analysis and immunohistochemical staining are in agreement in more than 90% of GCs [37].…”
Section: Microsatellite Instability In Gastric Cancermentioning
confidence: 70%
“…The histological features which are not specific, but are commonly seen, include an intestinal type of tumour and prominent lymphoid cell infiltration with expanding borders [26,37,38]. The MSI-H phenotype was also associated with mucinous GC or MUC 6 positivity [26,35]. There exists a growing body of evidence that GC with MSI is associated with a better prognosis than MSS GC [39,40].…”
Section: Microsatellite Instability In Gastric Cancermentioning
confidence: 99%
See 3 more Smart Citations